PENERAPAN IMAGE PROCESSING PADA ALAT PEMANEN ROYAL JELLY OTOMATIS - Fatchur Rozi Al Fitrah; Panca Mudjirahardjo; Eka Maulana (Jurnal Mahasiswa TEUB, 2022)
Royal Jelly is a nutritious food that has many benefits, thus increasing the demand for the product. Royal Jelly can be produced by bees 121 times/year, but the large amount of production is not matched by a good harvesting system, namely using the conventional method by prying out the queen cup. If the harvesting process is carried out in large quantities, farmers will have difficulties and have an impact on product quality, when the harvest time of royal jelly is getting longer, the quality of royal jelly will decrease, especially in the aspect of viscosity. Then an automatic royal jelly harvester is needed to speed up the harvesting process. In an automatic royal jelly harvester, a system that can detect and measure the distance of royal jelly is needed, namely by image processing using a camera. The results of the RGB segmentation test were obtained with a binary image thresholding value with a lower limit (220,220,220) and an upper limit (255,255,255) while the HSV method obtained a binary image thresholding value with a lower limit (0,0,240) and an upper limit (179,80,255). The detection rate of the HSV color space method gets 100% accuracy compared to the RGB color space method which gets 60%. In addition, measuring the distance of Royal Jelly with millimeters using a camera can be done using the Euclidean distance method and the percentage of error is relatively small (3%) from the actual distance.Keywords: Royal Jelly, Image Processing, Eclidean Distance